2014
DOI: 10.1111/cmi.12368
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial secreted effectors and caspase‐3 interactions

Abstract: Apoptosis is a critical process that intrinsically links organism survival to its ability to induce controlled death. Thus, functional apoptosis allows organisms to remove perceived threats to their survival by targeting those cells that it determines pose a direct risk. Central to this process are apoptotic caspases, enzymes that form a signalling cascade, converting danger signals via initiator caspases into activation of the executioner caspase, caspase-3. This enzyme begins disassembly of the cell by activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 90 publications
(164 reference statements)
2
26
0
Order By: Relevance
“…34 Caspase-3 activation during bacterial infection is also likely a common by-product of the coevolution of bacterial-host interactions, perhaps precipitated by the stress placed on host cells during invasion. [35][36][37][38][39] In addition to non-specific or indirect activation of caspase-3, bacterial effectors are also able to promote caspase-3 activation through subtle changes within cellular pathways or even through direct interaction with the enzyme. The outcome for the pathogenic intruder, such as S. Typhimurium is often an increase in infectivity rather than a clearing of the infection as expected by the conventional understanding of the protective role of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…34 Caspase-3 activation during bacterial infection is also likely a common by-product of the coevolution of bacterial-host interactions, perhaps precipitated by the stress placed on host cells during invasion. [35][36][37][38][39] In addition to non-specific or indirect activation of caspase-3, bacterial effectors are also able to promote caspase-3 activation through subtle changes within cellular pathways or even through direct interaction with the enzyme. The outcome for the pathogenic intruder, such as S. Typhimurium is often an increase in infectivity rather than a clearing of the infection as expected by the conventional understanding of the protective role of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Cyanobacterial caspase homologs have been previously found to be associated with WD40 repeats (Asplund-Samuelsson 2015). Their function in prokaryotes is largely unexplored, and in the host-associated context, they might play a role in bacterial pathogenesis and host interaction by mimicking eukaryotic caspases and promoting cell survival (Wall & McCormick 2014). Sialidases have been considered virulence factors in many pathogenic organisms, which colonize mucosal surfaces by hydrolysing the protective barrier and facilitating bacterial adhesion (Corfield 1992;Wiggins et al 2001).…”
Section: Domain Architecture Of Elps and Cotranscribed Proteinsmentioning
confidence: 99%
“…During apoptosis, pro-caspase-3 transforms to active enzyme when two cleaved monomers combine to form an active dimer. 40 Meanwhile, the balance between prosurvival Bcl2 and proapoptotic protein Bax is crucial for cell survival, and the ratio of Bcl2/Bax is becoming representative of cell apoptosis. 41 The present analysis of caspase-3 and Bcl2/Bax expression through Western blot showed that realgar NPs induced apoptosis in a dose-and time-dependent manner in K562 cells.…”
mentioning
confidence: 99%